Analisis Pemahaman Multikulturalisme Pada Tindakan Sosial Siswa - Sarbini; Muslimin (Indonesian Journal of Humanities and Social Sciences, 2021)
This article reviews the diversity that exists with respect and respect for students at SMPN 1 Kertosono. This article is a researcher's analysis of the relationship between understanding multiculturalism, social action, and student's level of understanding at SMPN 1 Kertosono. Their implications are social interactions that reflect multicultural values. The formulation of the problem in this journal, namely a) how is the diversity of citizens studying at SMPN 1 Kertosono, b) how are students' social actions with a multicultural spirit, c) how is the level of understanding of students at SMPN 1 Kertosono in multicultural social interactions. The method used in this study is descriptive qualitative with the results describing the reality of existing diversity with a good understanding of multiculturalism. Its implications for students' social actions reflect the value of multiculturalism.